2001
DOI: 10.1021/jf0101253
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Phenolic Compounds during Loquat Fruit Development

Abstract: Phenolic compounds in loquat fruit were identified as 5-caffeoylquinic acid (chlorogenic acid), neochlorogenic acid, hydroxybenzoic acid, 5-p-feruloylquinic acid, protocatechuic acid, 4-caffeoylquinic acid, epicatechin, o-coumaric acid, ferulic acid, and p-coumaric acid. Neochlorogenic acid was found to be dominant in the early stages of loquat fruit development. Both the concentrations and types of phenolic compounds were high in young fruit but then decreased steadily during growth. However, the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 24 publications
5
56
1
7
Order By: Relevance
“…Xu et al (2014) identified certain caffeic acid derivatives such as chlorogenic acid, neochlorogenic acid and 4-o-caffeoylquinic acid, together with protocatechuic acid, 4-hydroxybenzoic acid, caffeic acid, ferulic acid, ellagic acid, and ocoumaric acid in 6 cultivars of mature loquat fruits grown in China. Similar results were obtained by Ding et al (2001) and Ferreres et al (2009) who detected chlorogenic, and neochlorogenic acids among others phenolics Xu et al (2014) and Ercisli et al (2012) at mature stage.…”
Section: Bioactive Compounds Antioxidant Capacity and In Vitro Inhibsupporting
confidence: 88%
See 3 more Smart Citations
“…Xu et al (2014) identified certain caffeic acid derivatives such as chlorogenic acid, neochlorogenic acid and 4-o-caffeoylquinic acid, together with protocatechuic acid, 4-hydroxybenzoic acid, caffeic acid, ferulic acid, ellagic acid, and ocoumaric acid in 6 cultivars of mature loquat fruits grown in China. Similar results were obtained by Ding et al (2001) and Ferreres et al (2009) who detected chlorogenic, and neochlorogenic acids among others phenolics Xu et al (2014) and Ercisli et al (2012) at mature stage.…”
Section: Bioactive Compounds Antioxidant Capacity and In Vitro Inhibsupporting
confidence: 88%
“…TPC significantly decreased from 5.99 ± 0.15 to 3.24 ± 0.08 mg GAE g -1 DW when fruits changed from stage 1 to 2, remaining constant in the last maturity stage (3.41 ± 0.07 mg GAE g -1 DW, P>0.05). Ding et al (2001) found that total phenolic contents decreased by approximately 60% in loquat fruits in other cultivars when it passed from green to a colored state. Higher TPC values were found in mature fruit (0.46 mg GAE g -1 FW) compared to the results reported by Ercisli et al (2012) (0.14-0.25 mg GAE g -1 FW).…”
Section: Bioactive Compounds Antioxidant Capacity and In Vitro Inhibmentioning
confidence: 94%
See 2 more Smart Citations
“…Además, para una misma especie el contenido de fenoles es dependiente de la variedad (Ding et al, 1998b;Ding et al, 2001). En algunos frutos los niveles de fenoles aumentan a lo largo del desarrollo, alcanzándose los niveles más altos durante la recolección (Casado et al, 2003), mientras que para diferentes variedades el contenido de fenoles decrece hasta alcanzar el mínimo en el momento del cambio de color del fruto (envero) y después aumenta progresivamente alcanzando el máximo en la recolección.…”
unclassified